TOWARDS THE IDENTIFICATION OF SIDERITE, RHODOCHROSITE, AND VIVIANITE IN SEDIMENTS BY THEIR LOW-TEMPERATURE MAGNETIC PROPERTIES - Frederichs T.; von Dobeneck T.; Bleil U.; Dekkers M.J. (My University, 2003)
Siderite (FeCO3), rhodochrosite (MnCO3), and vivianite ([Fe3(PO4)2] · 8 H2O) are well-known authigenic minerals in a number of sedimentary settings. Here, we explore the potential of low-temperature mineral magnetic techniques for their identification at low concentration in bulk samples thus expanding mineral magnetic proxies for environmental purposes. The basic rock magnetic properties of these minerals, which are paramagnetic at ambient temperature, were determined with a ‘Magnetic Properties Measurement System’. Well-crystalline chemically analyzed material of natural origin was used to gather these data. The diagnostic value of the observed specific magnetic properties was tested on two mid-Eocene sediment samples from the Norwegian Sea (ODP Leg 104, Site 643) known to contain these minerals.